The Power of (Non) Positive Thinking: Self-Employed Pessimists Earn More than Optimists - Christopher Dawson; David Emmanuel de Meza; Andrew Henley; Reza Arabsheibani (Institute for the Study of Labor (IZA), 2015)
Developing further the accumulating evidence that self-employment attracts optimists, this paper investigates the relationship between earnings and prior optimism. It finds that self-employed optimists earn less than self-employed realists. Amongst employees, optimists earn more. These results are consistent with biased expectations leading to entry errors. As a test of validity, we find that amongst the married, future divorcees have higher financial expectations but their realisations are no worse, suggesting our optimism measure captures an intrinsic psychological trait associated with rash decisions.
Keywords: D84; M13; 330; financial optimism; expectations; self-employment